Modulation of the gut microbiota and lipidomic profiles by black chokeberry (Aronia melanocarpa L.) polyphenols via the glycerophospholipid metabolism signaling pathway - Zhu, Yue; Wei, Yu-long; Karras, Ioanna; Cai, Peng-ju; Xiao, Yu-hang; Jia, Cheng-li; Qian, Xiao-lin; Zhu, Shi-yu; Zheng, Lu-jie; Hu, Xin; Sun, Ai-dong (Frontiers in Nutrition, 2022)
Black chokeberry (Aronia melanocarpa L.) are rich in polyphenols with various physiological and pharmacological activities. However, the relationship between the modulation effect of black chokeberry polyphenols on obesity and alteration of lipid metabolism is not clearly understood. This study aimed to investigate the beneficial effects of the black chokeberry polyphenols (BCPs) treatment on structure of gut microbiota, lipid metabolism and associated mechanisms in high-fat diet (HFD)-induced obese rats. Here, we found that high-fat diet promoted body weight gain and lipid accumulation in rats, while oral BCPs supplementation reduced body weight, liver, white adipose tissue weight and ameliorated dyslipidemia and hepatic steatosis in HFD-induced obese rats. In addition, BCPs supplementation prevented gut microbiota dysbiosis by increasing the relative abundance of beneficial genus such as Bacteroides, Prevotella, Romboutsia, Akkermansia and decreasing the relative abundance of Desulfovibrio and Clostridium. Furthermore, 64 lipids were identified as potential lipid biomarkers through lipidomics analysis after BCPs supplementation, especially PE(16:0/22:6), PE(18:0/22:6), PC(20:3/19:0), LysoPE(24:0), LysoPE(24:1) and LysoPC(20:0). Moreover, our studies provided new evidence that composition of gut microbiota was closely related to the alteration of lipid profiles after BCPs supplementation. Additionally, BCPs treatment could ameliorate the disorder of lipid metabolism by regulating the mRNA and protein expression of genes related to glycerophospholipid metabolism signaling pathway in HFD-induced obese rats. The mRNA and protein expression of PPARα, CPT1α, EPT1 and LCAT was significantly altered after BCPs treatment. In conclusion, the results in this study indicated that BCPs treatment alleviated HFD-induced obesity by modulating the composition and function of gut microbiota and improving the lipid metabolism disorder via glycerophospholipid metabolism signaling pathway.